Kinerja keuangan industri transportasi sektor penerbangan pada masa pandemi covid-19 ditinjau dari rasio keuangan - Rizqi Ardiani, Silvia (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
The purpose of this study was to determine the financial performance of the aviation sector transportation industry during the Covid-19 pandemic in terms of financial ratios at PT AirAsia Indonesia Tbk and PT Garuda Indonesia Tbk in 2020. This study used a analysis descriptive qualitative method using secondary data in the form of reports financial statements and annual reports of PT AirAsia Indonesia Tbk and PT Garuda Indonesia Tbk from 2016 to 2020. The results of the study show that the company's short-term liquidity capability is getting lower. Both companies experienced a decrease in solvency work which can be seen from the negative DER value and the DR value more than 1 time. Profitability conditions seen from ROI during the Covid-19 pandemic experienced a very high rate of increase in losses. But ROE during the Covid-19 pandemic was profitable. As the impact of Covid-19, in 2020 PT AirAsia Indonesia Tbk and PT Garuda Indonesia Tbk experienced a decrease in total asset turnover almost touching zero, which means that the effectiveness of the use of total assets in the company is not good or the company's financial performance is low.